Federated States of Micronesia : Recent Economic Developments. (IMF Staff Country Reports; Country Report ;, 1998)
This paper reviews economic developments in the Federated States of Micronesia during 1994-97. Real GDP growth, which has been sluggish in recent years, contracted by 4 percent in FY1997. This mainly reflects a sharp reduction in government expenditures under the reform program implemented by the national and state governments since FY1996, the cornerstone of which is the reduction in workforce and wage levels of government employees. The 1996 official GDP data indicated that government services accounted for 42 percent of GDP, wholesale and retail trade for 22 percent, and agriculture, hunting, and forestry for 17 percent.